Ruido ambiental y comparación con el estándar nacional de calidad ambiental para ruido en la avenida participación - Belén, 2022 - Pereyra Culqui, Josué Juventino (2022)
The main objective of this study was to compare the levels of environmental noise with the national standard of quality of environmental noise that was evaluated in La Participación avenue in the Belén district-2022. The method used for this was the quantitative whose comparative descriptive research design of independent groups, with 93 samples, collected only on La Participación avenue in the Belén district, programmed for three different times, (morning, noon, and afternoon) using the Peruvian Technical Standard. The NTP ISO 1996-2 specification procedure used a Class 1 sound level meter as the measuring instrument. The results obtained in the said road, the vehicular traffic in the morning (7:00 - 9:00) spend an average of one hour 867 motorcycles, 1551 motokar and 102 cars, at noon (12:00 - 14:00) they pass in an average of one hour 885 motorcycles, 1331 motokar and 75 cars, in the afternoon (17:00 - 19:00) spend an average of one hour 1009 motorcycles, 1317 motokar and 84 cars, in the same way 61 commercial activities were identified and 75 activities that provide services, considering fixed sources of noise emission. However, an average noise level has been obtained in the morning of 78.3 dB, at noon of 77.9 dB, in the afternoon of 78.1 dB, whose P-value making the contrasts with the independent sample T-test with the environmental quality standard for noise and the urban development plan of the province of Maynas, a value of 0.000 has been obtained. whose conclusion the general hypothesis is accepted according to the contrast with the inferential test, due to the existence of fixed and mobile sources that generate noise above the environmental quality standard for noise.